A comparative study of major histocompatibility complex antigens in East African and European cattle breeds - Kemp, Stephen J.; Spooner, R.L.; Teale, A.J. (Wiley, 1988)
Summary.An account is given of the serologically defined class I specificities encoded by the bovine MHC (expressed as the BoLA system) in two populations of African cattle and in European breeds.The BoLA typing was performed using alloantisera raised against tissue antigens of both European and African breeds of cattle. All of the specificities agreed in the first two international BoLA workshops were found in the African cattle, although there were significant differences in the frequency of some specificities between the African and European animals. Many of the European antisera, which are operationally monospecific in Bos taurus cattle, were multispecific in the African animals.Subgroups of two specificities (w8 and w10) were demonstrated. Five new BoLA‐A locus alleles were detected by means of antisera raised against alloantigens of African cattle. Two of these occurred at an extremely high frequency in the African populations; one being unique to these cattle. Monoclonal antibodies proved to be useful typing reagents, particularly in the elucidation of subgroups.